Non-technical skills for surgeons, the NOTSS (Journal of Patan Academy of Health Sciences, 2018)
The cognitive and social skills are important categories of ‘nontechnical skills (NTS)’ for surgeons’ performance and is increasinglybeing appreciated and accepted widely.1 Adverse events duringhospital stay occur in up to 10-17% patients, half of which can beprevented because they occur not for the lack of knowledge,technical skills or equipment but simply due to failure of NTS.Surgery (39.6%) and medication (15.1%) related events accounts formajority of these adverse events. Errors in  nonoperativemanagement are responsible and causes more adverse events thansurgical technique. In a review of fatal medical accidents by the Japan Medical SafetyResearch Organization categorized the events into technical skills,NTS and inevitable progress of disease. It revealed that the causesof deaths were NTS in 34 (46.6%), disease progression in 33 (45.2%)and only in 2 (5.5%) due to technical skills and 2 (5.5%)undetermined. Further analysis of NTS revealed that the causes ofdeaths in 33 (97.1%) cases were due to errors in three areassituationawareness 14 (41.2%), team work 8 (23.5%) and decisionmaking 3 (8.8%). Thus, training in certain specific subcategories ofNTS may effectively reduce adverse events. The NTS behavior includes ‘cognitive, social and personal skills’ thatcomplement technical skills for safe and efficient task performanceof individual and team in care of patients.5,6 The surgical NOTECHSbehavioral marker includes four categories- ‘leadership andmanagement, teamwork and cooperation, problem solving anddecision making, situation awareness among sub-team (of nurses,surgeons and anesthetists)’ and are important part of surgical skillsnecessary for surgeons and the team to become aware to managetheir situation appropriately.